Performance analysis of submerged aerated biofilm (Biokube Jupiter 50) system in municipal wastewater treatment / Nur Azrinawati Ab Rahman - Ab Rahman, Nur Azrinawati (2010)
Performance analysis of submerged aerated biofilm (Biokube Jupiter 50) system (SABS) in municipal wastewater treatment was studied. The samples were taken from wastewater treatment plants at Mawar College, UiTM. The study was focused on the characteristic of wastewater treated by the SABS, the efficiency and the effectiveness of the SABS in treating domestic wastewater. A comparative performance study was made between SABS and Extended Aeration Activated Sludge System (EAASS). It is found that the wastewater was in a low strength and able to treated by biological process. SABS efficiently removed 40% to 60% of PO4-P, 85 to 98% of COD, 60 to 90% of BOD5 and 90 to 98% of SS. The SABS also efficiently removed ammonia due to high increment of NO3-N at the end of the process. Furthermore, SABS was efficiently complied with the new revised Malaysian effluent standard. The performance of SABS was effective during variation of incoming loading. By comparing with EAASS, SABS was more efficient and effective in treating domestic wastewater.